Development of Hypereutectic AlSi Alloy Powder Injection Molding Feedstocks by Rheological Analysis - Jiaqi Ni; Keqing Han; Muhuo Yu (Advances in Materials Science and Engineering)
The comprehensive properties of a feedstock have a critical influence on the powder injection molding process. Proper feedstock with homogeneous structure, favorable flow characteristic, and moldability is the prerequisite for obtaining a final part with excellent comprehensive properties. The objective of the present work was to develop an optimal feedstock for fabrication of hypereutectic AlSi (20 wt.%) alloy parts by the powder injection molding technique. For this purpose, micron-sized hypereutectic AlSi (20 wt.%) alloy powder was mixed with different amounts of a binder which consisted of 35 wt.% high-density polyethylene, 62 wt.% carnauba wax, and 3 wt.% stearic acid. The binder contents of the feedstocks were in the range from 13 wt.% to 21 wt.%. The influences of binder content, shear rate, and temperature on the rheological behaviors of feedstocks have been investigated via a capillary rheometer. The feedstock with 21 wt.% binder exhibited a variable flow behavior and was culled. The rest of the feedstocks showed a pseudoplastic behavior. Comprehensive analysis of rheological parameters such as the flow behavior index, yield stress, flow activation energy, and the general moldability index, the feedstock with 17 wt.% binder exhibited the best rheological performance and favorable moldability. The molded part with 17 wt.% binder had constant density, good shape retention, and stiffness as well as homogeneous distribution of the powder and binder. After solvent debinding, the debound item showed a homogeneous porous structure which is suitable for the subsequent thermal debinding and sintering processes.